The Miocene stratigraphy of the Laberinto area (Río Ica Valley) and its bearing on the geological history of the East Pisco Basin (south-central Peru) - DeVries T.J. (2021)
JAB received funding from the United States Geological Survey , Climate Research and Development Program , for this study. DO was supported by CONCYTEC (Peru) research grants CB ( N° 105-2018 - FONDECYT ) and “Incorporación de Investigadores” ( N° E038-2019-02-FONDECYT-BM ). RE was supported by Geosciences Research Institute grant GRI19-1 . LWS was supported as an employee of the United States Geological Survey during the 1980s. TJD and MU did not receive any grant from funding agencies in the public, commercial, or not-for-profit sectors.